Chronic kidney disease and subclinical lacunar infarction are independently associated with frontal lobe dysfunction in community-dwelling elderly subjects : the Sefuri brain MRI study - Yao, Hiroshi; Miwa, Yoshikazu; Takashima, Yuki; Yahara, Koji; Hashimoto, Manabu; Uchino, Akira; Yuzuriha, Takefumi; Sasaguri, Toshiyuki (Hypertension research, 2011)
Although recent studies have found that chronic kidney disease (CKD) is an independent risk factor for cognitive impairment in population-based cohorts, the mechanisms of cognitive impairment in subjects with CKD are unclear. We examined 503 elderly subjects (mean age: 72.4 years), who were living independently at home without apparent dementia, using MRI. The subject was judged as having frontal lobe dysfunction if the scores on the modified Stroop test were higher than the fifth quintile for each given decade. Serum creatinine values, measured by the enzymatic method, were used for the Japanese equation of estimated glomerular filtration rate (eGFR). Subjects in the frontal lobe dysfunction group tended to have higher blood pressure, lower eGFR and more lacunar infarcts, and were less educated. When possible confounders were entered into the multivariate logistic regression model, the independent predictors of frontal lobe dysfunction were eGFR (odds ratio 0.854; 95% confidence interval (CI) 0.743–0.983 per 10 ml min −1 per 1.73 m 2 ) and the number of lacunar infarction (odds ratio 1.460; 95% CI 1.127–1.892). The mean of the logarithmically transformed Stroop test scores in the eGFR<60 ml min −1 per 1.73 m 2 group was 1.376 (95% CI 1.301–1.451), which was significantly higher than that (1.250) for the eGFR 60–89 ml min −1 per 1.73 m 2 group (95% CI 1.215–1.285) ( P =0.009) and tended to be higher than that (1.264) for the eGFR ⩾90 ml min −1 per 1.73 m 2 group (95% CI 1.188–1.340) (analysis of covariance, adjusted for age). The present study showed that CKD and subclinical lacunar infarction independently contributed to frontal lobe dysfunction in healthy elderly subjects.